Use promazine hydrochloride in labor analgesia - Lozano Pardo, José (2015)
In a study of 160 cases shows that the Hydrochloride promazine (*) is a valuable new agent, associated with other drugs known action in analgesic therapy delivery, it potentiates the effect and acts as an excellent sedative and anti -emético without interfering with the normal progress of labor not mean risk to the mother or fetus. Because in the case of deeply sedated gilts lack of cooperation is seen during the second stage, the use of this drug is not recommended except in specialized hospital environments where you can count on, if necessary, with their own resources to resolve a any extension of that period.